Localization versus subradiance in three-dimensional scattering of light - Moreira, Noel Araujo (2019)
A blue sky, a white cloud or a red sunset are explained by classical multiple scattering theory of light. However, these phenomena neglect interference occurrence. Once it is taken into account, interference in a disordered medium may actually put a halt to the propagation of light, an effect known as Anderson Localization. Until now, experimental reports of Anderson Localization of light in 3D systems have not been conclusive. Our goal is to understand what are the underlying obstacles, and look for new insights from a theoretical point of view. In this dissertation, the properties of a cloud of two-level atoms scattering light are investigated. The dipole-dipole interaction generates collective modes, some of them, being localized. We found that finite-size effects dominate the lifetime of the localized modes, specifically by the ratio of localization length to their distance to the system boundaries. Localized modes saturates at maximum of 20% even above phase transition. Studying the steady-state regime, the coupling between localized modes and light is weak. Both results agrees with the difficulty of experimental evidence of light localization and promote the link of experiments and theory.